2016
DOI: 10.1016/j.schres.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive–compulsive symptoms interact with disorganization in influencing social functioning in schizophrenia

Abstract: Data suggest that in patients with schizophrenia, functioning at least in part depends on the interaction between disorganization and OCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…73 The rsFC between the left fusiform gyrus and the medial oFG correlated inversely with Y-BOCS compulsive behavior subscale scores in patients with SOC, suggesting that obsessive behavior may be a reflection of neural adaptation, ie, a compensatory effect in patients with SOC. 17 A similar mechanism has been found in generalized anxiety disorder and PTSD patients. 74 Another important observation in this study is that patients with SOC exhibited significantly decreased rsFC between the DMN and the SN, particularly between DMN subregions and the SMA.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…73 The rsFC between the left fusiform gyrus and the medial oFG correlated inversely with Y-BOCS compulsive behavior subscale scores in patients with SOC, suggesting that obsessive behavior may be a reflection of neural adaptation, ie, a compensatory effect in patients with SOC. 17 A similar mechanism has been found in generalized anxiety disorder and PTSD patients. 74 Another important observation in this study is that patients with SOC exhibited significantly decreased rsFC between the DMN and the SN, particularly between DMN subregions and the SMA.…”
Section: Discussionsupporting
confidence: 54%
“…12 One study has reported a dual impact of OCD on functioning in SCZ with a gradual transition from an improving to a worsening effect depending on OCD symptoms severity. 17 Neuroimaging findings have shown that patients with SOC could have smaller whole brain gray matter volume, 18 smaller hippocampal volume, 19 and enlarged anterior horn of the lateral ventricles. 20 These results support the "double jeopardy hypothesis" of SOC.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the close relationship between obsessive–compulsive symptoms and schizophrenia, a previous study regarded obsessive–compulsive symptoms as a buffer that may help to prevent the emergence of psychosis during the prodromal period (Pious, 1950). Recent studies have speculated that specific obsessive themes may confer a certain functional order and stability that counterbalances the functional impairment caused by the underlying thought and behavioral disorganization process (Tonna, Ottoni, Paglia, Monici, et al, 2016; Tonna, Ottoni, Paglia, Ossola, et al, 2016). Meanwhile, there is also an overlap between delusional and obsessive phenomena, causing difficulties in identifying obsessive–compulsive symptoms (Tezenas du Montcel, Pelissolo, Schurhoff, & Pignon, 2019).…”
mentioning
confidence: 99%
“…Diagnostic criteria for a schizo-obsessive subgroup of schizophrenia has been proposed [47], and a reverse U-shaped curve between the obsessive-compulsive dimension and functioning in schizophrenia patients might model this relationship [48]. Nevertheless, the disorganization dimension appears to be the most relevant dimension, moderating this complex psychopathological observation [49].…”
Section: Discussionmentioning
confidence: 99%